An Index Description of the General Characteristics of Thermospheric Density Based on the Two‐Line‐Element Data Sets and the Spectral Whitening Method - Wu, Yihan; Mao, Tian; Wang, Jing‐Song; Tang, Wei; Song, Qiao; Zhao, Ming‐Xian (Journal of geophysical research. Space physics, 2024)
The thermospheric density and its variations are crucial to aerospace activities as well as space weather research and operation. However, due to the difficulties in observing the thermosphere, there has been a lack of effective descriptions for the general characteristics of thermospheric density. In this paper, the Two‐Line‐Element data sets (TLEs) from multi‐target low Earth orbit satellites are used to derive a proxy of the daily average atmospheric density in the thermospheric shell located in the vicinity of LEOs' orbital altitude. It captures the overall characteristics of the thermosphere and exhibits good correlations (∼0.9) with modeled and observed thermospheric density. By applying the spectral whitening method to this proxy, a new index JsT ${J}_{s}^{T}$ is derived to describe non‐periodic perturbation of the density where the specific satellite passed by. The fact that the JsT ${J}_{s}^{T}$ obtained from different satellites within the same thermospheric shell presents significant consistency to each other means that the new index is a good indicator for the overall feature of the variations of thermospheric density, and it is possible to define a unified regional index JrT ${J}_{r}^{T}$ to describe density disturbances for the thermospheric shell where these satellites fly through. Moreover, the JrT ${J}_{r}^{T}$ at different altitudes also present good consistency suggesting the possibility of defining a global index JpT ${J}_{p}^{T}$, capable of describing the density variation of the entire thermosphere. Plain Language Summary Due to limited in situ observation, the thermospheric density is not easy to obtain. Herein, we have extracted the density information of the thermosphere based on the Two‐Line‐Element data sets and developed a new index using the spectral whitening method, which describes aperiodic disturbances of the density. The construction of this index series can address the limitations of existing quantitative or graded descriptions of space weather disturbances and the problem of mismatched or inconsistent parameters/indices. Ultimately, this will contribute to the monitoring and warning of space weather causal chains. Key Points A proxy of daily average thermospheric mass density was extracted from Two‐Line‐Element data sets By applying the spectral whitening method to this proxy, a new index is derived to describe non‐periodic perturbations in the thermosphere A unified regional index was defined to describe density disturbances for the thermospheric shell where these satellites fly through